The Effectiveness of Using Team-Pair-Solo to Students’ Reading Comprehension - Sugiharti, Sri; Wilany, Eka; Vintaria, Yenny (English Department, University of Riau Kepulauan, Batam,Indonesia, 2017)
The objective of the research was to find out whether team-pair-solo is effective to students’ reading comprehension. The research design was quantitative research with experimental design. The research conducted in August 2016. The population in this research was the eleventh grade students of SMA K Yos Sudarso Batam in the academic years of 2016/2017. Two classes were selected two from the population as sample in this study they were XI A2 and XI A3. The number of the students used as the sample in this research was 60 students. The sample was selected cluster sampling technique. To identify student competence, the writer gave the test before treatment (pre-test) and after treatment (post-test). The result of data analyzing was shown that in after test the mean of experiment class was higher (77.16) than control class (63.83). In the end of hypothesis testing, the writer found that there was significant effect of team-pair-solo to students’ reading comprehension. It means that team-pair-solo able to encourage the students to comprehend the text well